Pentingnya Kapabilitas Inovasi dalam Meningkatkan Performa Bisnis - Nyoman Surya Wijaya; Putu Laksmita Dewi Rahmayanti; I Made Darsana; Miko Andi Wardana (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
This study aims to explain how the role of innovation capabilities in entrepreneurial orientation in influencing business performance. The population of this study consists of MSMEs in Bali's tourism and creative economy (parekraf) industry. Purposive sampling was used to select 90 MSME managers in the tourism and creative economy sectors. Path Analysis with SEM-PLS is used as an analytical approach. The findings show that there is a positive and significant impact of entrepreneurial orientation on business performance shown by creativity, innovation, dare to take risks, be independent, and dare to compete. The positive and significant influence of entrepreneurial orientation on innovation capabilities; and the positive and significant influence of innovation capabilities on business performance. Innovation capabilities are able to mediate the influence of entrepreneurial orientation on business performance. Therefore, it is important for MSMEs in the tourism sector and creative economy in Bali to improve entrepreneurial orientation in order to be able to build higher innovation capabilities to improve business performance after the COVID-19 pandemic.